Gambaran Tingkat Kecemasan dan Tekanan Darah pada Pasien Hipertensi: Literature Review - Kudung Wulan Sari; Trina Kurniawati (Prosiding University Research Colloquium, 2022)
An increased blood pressure can be affected by fear, discomfort, and anxiety. The impact on hypertension can lead to heart attacks, strokes, and even death. Patients with hypertension can prevent their blood pressure from increasing. The hypertensive patients should go on a sodium salt diet and low cholesterol diet. They also should avoid stress and anxiety. This study aimed to describe the level of anxiety and blood pressure in hypertensive patients through a literature review. The data collection technique used a literature review method of 5 articles from online databases through Google Scholar searches and Garuda Portal published in 2011-2021. The critical analysis instrument used was the Hawker instrument. In the anxiety category, from the five articles, there were 119 respondents who experienced moderate anxiety. In the category of blood pressure level, in articles 1 and 2, 45 respondents had moderate blood pressure, 35 respondents had mild blood pressure in articles 3 and 5, 24 respondents had mild blood pressure, and 24 respondents had severe blood pressure. Conclutions based on the results, it shows hat that anxiety can affect blood pressure.